The Effect of Gratitude, and Self-Awareness on the Happiness of Islamic Boarding School Students - Primaheni, Firda; Purwanto, Edy; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2021)
Teenage students complain about their lives at Islamic boarding schools with limited facilities and busy activities which are certainly different from life when they are at home with their families. An unpleasant life, truant, and not comfortable because they have not been able to adapt. This study was designed to examine the effect of gratitude and self-awareness on the happiness of adolescent students at Islamic boarding schools. A total of 155 teenage students aged 14-19 years from two Islamic boarding schools in Pemalang were selected as participants using a random sampling method. The data were taken using the accumulated gratitude scale, self-awareness scale and adaptation of the adolescent happiness scale at boarding school from Roger Morgan. The data were then analyzed using the SPSS version 25.00 computer program. Statistical results show that there is a positive influence between gratitude on the happiness of adolescent students, and there is a positive influence between self-awareness on the happiness of adolescent students. The findings of this study recommend increasing the happiness of students through gratitude and self-awareness.